Palm-size portable printer with bluetooth and scanner / Roslayni Misran, Amirah Nur Syahirah Abd. Ghafur and Aina Jihan Muhammad Nurul Azmi - Misran, Roslayni; Abd. Ghafur, Amirah Nur Syahirah; Muhammad Nurul Azmi, Aina Jihan (2017)
The team is developing a device that is small portable printer with Bluetooth and scanner. This will be a new to the world product whereby the device can be connected to the smartphones.